COMMENTS ON EUROPEAN GUIDELINES ON THE MANAGEMENT OF STABLE ANGINA PECTORIS (2006) - S. Y. Martsevich (Racionalʹnaâ Farmakoterapiâ v Kardiologii, 2015)
Comments on European Guidelines on the management of stable angina pectoris (2006).